Benefits of Cooking Shows on Youtube for Students of Casinology of Indonesia University of Education During A Pandemic - Ellis Endang Nikmawati; Rula Kaamila Imanadi; Ai Mahmudaatulsaadh (Journal of Architectural Research and Education, 2022)
Abstract - Distance learning implemented during the pandemic emphasizes independent learning and utilizes various kinds of learning resources that are around students. One of the learning resources that can be used is Youtube. Youtube can help the lectures of Culinary Education students at the Indonesia University of Education in completing one of their courses, namely Cipta Boga which requires various inspirations in food processing because Youtube has many cooking shows that can be used as a place to find inspiration. The purpose of this study is to find out the benefits of cooking shows on Youtube for students of the Indonesia University of Education's Culinary Education during the pandemic in the Cipta Boga course. The data collection technique was carried out by distributing questionnaires to students of the Indonesian University Culinary Education class of 2018. The population in this study was 45 people and the sample in this study was the entire population of 45 students of the Indonesian University of Education Culinary Education class 2018. The results showed that the intensity of using the internet, Youtube, and cooking shows during the Cipta Boga course was very frequent. Furthermore, the intensity of watching shows on cooking channels and food reviews that have been listed is never. Then, the intended use of the media that has been listed is very high. Next, the benefits in terms of knowledge and skills are very high. While the benefits in terms of attitude are quite high. Keywords: Benefits, Cooking Videos, Youtube, Student